THE COMPARATIVE EFFECTIVENESS OF INTENSITY-MODULATED RADIOTHERAPY (IMRT) IN CANCER TREATMENT: SYSTEMATIC REVIEW - Nazhifah, Naurah; Nurhidayat, Wahyudi (Jurnal Kesehatan Tambusai, 2024)
Intensity-Modulated Radio Therapy (IMRT) are often used to treat cancer because of its advantages and low risks. This study aims to investigate the evidence supporting the routine use of IMRT in various cancer in the aspects of conformity and homogeneity indices, toxicity, quality of life, and life expectancy. This is a systematic review which examines articles published from 2019 – 2024 in Google Scholar, Proquest, Elsevier, Portal Garuda and local journals databases. Article searched using keywords like Radiotherapy, Intensity-Modulated Radiotherapy, Effectiveness of Intensity-Modulated Radiotherapy, and comparison of Intensity-Modulated Radiotherapy. This study found the superiority of IMRT compared to other methods in the aspects of achieving conformity and homogeneity indices, toxicity, quality of life and life expectancy.